Black Box Testing dengan Teknik Equivalence Partitions Pada Aplikasi Android M-Magazine Mading Sekolah - Elfina Novalia; Apriade Voutama (SYNTAX Jurnal Informatika, 2022)
Application/software testing is a stage to check whether a program is running properly or not. One of the software that needs to be tested is the M-Magazine application. M-Magazine is an android-based application that is used as a digital magazine in high school which consists of two parts, namely website-based as an admin panel and mobile-based which is used on mobile users' devices. Testing is done using Black Box with Equivalence Partitions technique. Black Box testing is used to see whether the program is in accordance with the program function without knowing the program code, while the technique used is Equivalence Partitions which is a testing technique based on entering data in each form or page of the M-Magazine application, each input value will be tested and grouped according to the test. case where the result is valid or invalid. The purpose of testing on the M-Magazine Application is to detect and minimize failures when implemented so that errors found can be corrected more quickly.